ANALISIS EKONOMI PERBANDINGAN PENGGUNAAN ALAT COAL CRUSHER DAN FIXED SCREEN DALAM KEGIATAN COAL GETTING - Muhammad Faisal Seprizal; Machmud Hasjim; Restu Juniah (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
Coal getting is one of the activities involved in mining operations. PT. Manggala Alam Lestari, Indonesia carrying out coal getting activities by including in pit coal processing, namely selecting the size or sizing of coal using a fixed screen or grizzly screen. However, the use of fixed screen needs to be analyzed from an economic point of view by comparing with other coal processing processes. This study aims to conduct an economic analysis by comparing investment in coal crusher with fixed screen in coal getting activities. The results showed that coal crusher investment has a Net Present Value (NPV) value of Rp. 751,513,587,600, Internal Rate of Return (IRR) of 10.0279%, Profitability Index of 55.4 and Payback Period of around 0.36 years (4.3 months). Then, fixed screen investment has a Net Present Value (NPV) value of Rp. 709,285,734,051.00, Internal Rate of Return (IRR) of 10.0273%, Profitability Index of 528.1 and Payback Period of around 0.27 years (3.29 months. Fixed screen can still be the main choice because it has a lower investment value than coal crusher so that the resulting profit is also greater.